High quality biodiesel obtained through membrane technology - Atadashi, I.M.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (2012)
In this study, a ceramic membrane with a pore size of 0.02Î¼m was used to purify crude biodiesel to achieve biodiesel product that meet both ASTM D6751 and EN 14241 standards specifications. The membrane system was successfully developed and used for the purification process. Process operating parameters such as transmembrane pressure, flow rate and temperature were investigated. Application of central composite design (CCD) coupled with Response Surface Methodology (RSM) was found to provide clear understanding of the interaction between various process parameters. Thus, the process operating parameters were then optimized. The optimum conditions obtained were transmembrane pressure, 2bar, temperature, 40Â°C and flow rate, 150L/min with corresponding permeate flux of 9.08 (kg/m 2h). At these optimum conditions, the values of free glycerol (0.007wt) and potassium (0.297mg/L) were all below ASTM standard specifications for biodiesel fuel. In addition the physical properties of biodiesel at the optimum conditions met both ASTM D6751 and EN 14214. This work showed that with ceramic membrane of pore size 0.02Î¼m, biodiesel with high qualities that meet the stringent standards specifications more than those currently in application can be achieved. Â© 2012 Elsevier B.V.